A Literature Review of Social and Economic Leader–Member Exchange - Andersen, Ingvild; Buch, Robert; Kuvaas, Bård (Frontiers in Psychology, 2020)
Leader–member exchange (LMX) research has increasingly relied upon the social exchange theory (SET) as a theoretical foundation, but the dominating way of measuring LMX has not followed this theoretical development (Gottfredson et al., 2020). With the aim of developing a measure that more coherently reflects SET, Kuvaas et al. (2012) conceptualized LMX as two qualitatively different relationships, labeled economic LMX and social LMX. Since the most applied LMX measures are under scrutiny for not being sufficiently grounded in theory (Gottfredson et al., 2020), it may be especially important to expose alternative measures. Therefore, we provide a comprehensive review of the research to date applying a two-dimensional approach to LMX, while also adding to interpretation and suggestions for how we can progress the field even further.